Pancasila sebagai Landasan Pendidikan dan Penanggulanggan Pengangguran - R. Mumu Abdul Muthi; Ridha Aviani; Supriyono Supriyono (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research raises the topic "Pancasila as a Foundation for Education and Overcoming Unemployment" with the aim of understanding the foundation of education in Pancasila. Through literature study methods, we have identified Pancasila, education and unemployment. Pancasila is the ethics and morals of the Indonesian nation in the sense that it is the common core of the various morals that are actually found in Indonesia that are able to overcome all factionalism in Indonesia. Pancasila is the basis of the national philosophy as well as the Indonesian nation's philosophy of life, in fact it is a systematic, fundamental and comprehensive set of values. So silila is a unity that round and intact, hierarchical and systematic. The results of this research highlight the importance of understanding and maintaining values in the context of Pancasila in order to strengthen the moral and ethical foundations of Indonesia's national development.